The method and practice of clinical teaching for nursing students in the endocrinology department of Traditional Chinese Medicine hospital (中医院内分泌科实习护生临床带教方法研究与实践) - YUAN Zheng (袁铮); CHEN Yuanyuan (陈媛媛); LI Wei (李伟) (中西医结合护理)
Objective To investigate the method and practice management of clinical teaching for nursing students in the endocrinology department of a certain Traditional Chinese Medicine(TCM) hospital, and to provide reference for quality improvement of nursing teaching and practice. Methods According to the method of clinical teaching, Totally 100 nursing students who participated in the internship during June 2019 and June 2021 were divided into the control group (n=20, receiving conventional teaching) and observation group (n=20, receiving case-based teaching). All nursing students participated in the final assessment consisting of theoretical and practical test at the end of internship. A self-made questionnaire was used to investigate the students ‘satisfaction with clinical teaching. Results Nursing students in the observation group achieved higher scores of theoretical and practical tests than those in the control group, with a significant difference (P＜0. 01). The score of satisfaction assessment in the observation group were higher than that in the control group, with a significant difference (P＜0. 01). Conclusion The case-based teaching method is effective to improve nursing students’ motivation in learning and clinical practice skills. (目的 探讨中医院内分泌科实习护生临床带教方法, 提高内分泌科临床教学质量。方法 将 2019 年 6月—2021 年 6 月内分泌科接收的中医院校本科实习护生100例为研究对象。根据教学方式不同分为两组: 对照组50例, 采用传统护理带教模式; 观察组50例, 采取基于案例教学法的护理带教模式。两组护生均于实习结束参加考核, 包括理论测试和中医护理技术操作。采用自制问卷调查实习护生满意度。结果 观察组实习护生专科理论知识和中医护理操作技能考核评分均高于对照组, 差异有统计学意义(P＜0. 01) 。观察组实习护生对临床带教满意度评分高于对照组, 差异有统计学意义(P＜0. 01)。结论 采取基于案例教学法的护理带教模式, 能够提高实习护生学习积极性, 提高临床实践能力。)